Skulptur-Konzept. - Hoppe-Sailer, Richard (Krefeld : Galerie Ludwig, 1992)
Andre, Carl ; Cabrita Reis, Pedro ; Cragg, Tony ; Flavin, Dan ; Judd, Donald ; Long, Richard ; Mundt, Wilhelm ; Rückriem, Ulrich ; Spitzer, Serge ; Whiteread, Rachel
Skulptur-Konzept, Galerie Ludwig, Krefeld, 17. Mai bis 31. Juli 1992
boek